Welche Geschlechtsvorstellungen erzeugen nicht-referenzielle (generische) Maskulina? Zum Einfluss von Stereotypen und Grammatik - Bröder, Hannah-Charlotte; Rosar, Anne (Linguistik Online, 2025)
This study explores the gender representations evoked by non-referential (generic) masculine nouns and examines the impact of linguistic and extralinguistic factors including number, the distinction between occupational and non-occupational roles, gender stereotypes, and participants’ gender. Therefore, an online cloze experiment with naming tasks (given names) was conducted (e. g., “A hairdresser usually does not work on Mondays. On that day, ___ goes jogging, but ___ makes an exception and opens the salon”). The results indicate that masculine generics possess gender-inclusive potential, but only under specific conditions: Women are more likely to be considered when referring to stereotypically female roles (such as Katzenbesitzer ‘cat owner’, Kindergärtner ‘kindergarten teacher’) and plural forms, whereas male stereotypes (Programmierer ‘computer programmer’, Motorradfahrer ‘biker’) – especially in the singular – resist gender-inclusive readings. Men are more likely than women to interpret generic masculines as exclusively male. Additionally, English loanwords (Blogger, Manager) do not differ significantly from native German words in interpretation. Androcentric stereotypes also interact with labels for regional origin (Kölner ‘citizen of Cologne’, Sachse ‘Saxon’), which are predominantly perceived as male. Religious labels for out-groups (Jude ‘Jew’, Muslim) evoke male readings, while Christ (in-group) is perceived as gender-balanced. Overall, a male-first bias was observed, with male names filling the first blank more often.